Diverging Ozone Trends Above Western North America: Boundary Layer Decreases Versus Free Tropospheric Increases. Issue 8 (12th April 2023) - Chang, Kai‐Lan; Cooper, Owen R.; Rodriguez, Gavin; Iraci, Laura T.; Yates, Emma L.; Johnson, Matthew S.; Gaudel, Audrey; Jaffe, Daniel A.; Bernays, Noah; Clark, Hannah; Effertz, Peter; Leblanc, Thierry; et al.
Abstract: This study has produced an improved percentile and seasonal (median) trend estimate of free tropospheric ozone above western North America (WNA), through a data fusion of ozonesonde, lidar, commercial aircraft, and field campaign measurements. Our method combines heterogeneous data sets according to the consensus data characteristics and inherent uncertainty in order to produce our best fused product. In response to different data collection environments (in situ or ground‐based), we investigate the ozone variability based on a wide range of percentiles, which is preferable for trend detection due to tropospheric ozone's high degree of heteroscedasticity (i.e., inconsistent trends and variability between different ozone percentiles). We then compare the ozone trends and variability above the California sub‐domain to the full WNA region for better understanding of the correlations between different regional scales. In California, the 1995–2021 percentile (from the 5th to 95th) and seasonal trends are clearly positive in terms of high signal‐to‐noise ratios. The magnitude of the trends is generally weaker over WNA compared to California, but reliable positive trends can still be found between the 10th and 70th percentiles, as well as winter and summer, whereas autumn shows a negative trend over the same period. In addition, dozens of rural surface sites across the region are selected to represent the boundary layer variability. In contrast to increasing free tropospheric ozone, we find overall strong negative surface trends since 1995, with the greatest divergence found in summer. Throughout the analysis implications of the COVID‐19 economic downturn on ozone variability are discussed. Plain Language Summary: Free tropospheric ozone above western North America has increased since the mid‐1990s. Despite an observed drop of ozone in 2020 due to the COVID‐19 economic downturn, this observation‐based study shows the overall free tropospheric ozone trends have not been offset and continued to increase over 1995–2021, mainly driven by strong positive trends in winter and summer. In combination with the strong negative trends observed at rural surface sites over the same period, this study adds to the growing body of evidence that surface trends are frequently disconnected from the general increases observed in the free troposphere. Key Points: The median free tropospheric trend above western North America (1995–2021) remained positive despite the COVID‐19 economic downturn in 2020 Stronger positive ozone trends in all seasons and nearly all percentiles are found above the California subdomain In contrast ozone is decreasing at rural surface sites, especially at the 95th percentile